Answer:
Explanation:
To solve this you need to solve each side of the equation first. Let's start with the right side.
3(2x + 1) = ? (Distribute the 3)
6x + 3 = ? (Subtract the 3 from each side of the equation.)
6x = -3 (Divide by 6 on each side)
x = -1/2
Now lets solve the other side.
2(2x + 1) = ? (Distribute the 2)
4x + 2 = ? (Subtract 2 from each side of the equation.)
4x = -2 (Divide by 4 on each side of the equation)
x = -1/2
Both equations have equivalent x values therefore it can't be no solution.
Now plug in a different value to see if it's infinite.
3(2(1) + 1) = 2 (2(1) + 1)
9 = 6
Therefore it can't be infinite equations, there is one solution.